2014
DOI: 10.1121/1.4900831
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing frequency-to-electrode allocation for individual cochlear implant users

Abstract: 1Individual adjustment of frequency-to-electrode assignment in cochlear implants may 2 potentially improve speech perception outcomes. Twelve adult cochlear implant (CI) 3 users were recruited for an experiment, in which frequency maps were adjusted using 4 insertion angles estimated from post-operative X-rays; results were analyzed for ten 5 participants with good quality X-rays. The allocations were a mapping to the 6 Greenwood function, a compressed map limited to the area containing spiral ganglion 7 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…This raises the question of whether CIs could be fitted with the goal of mitigating the effect of decreased spectrotemporal resolution that may arise from channel interaction. Several studies (e.g., Di Nardo et al., 2011 ; El Boghdady et al., 2018 ; Fitzgerald et al., 2013 ; Fu & Shannon, 1999 ; Grasmeder et al., 2014 ; Leigh et al., 2004 ; McKay & Henshall, 2002 ; Omran et al., 2011 ) have proposed that optimizing the frequency-to-electrode allocation map could have the potential to address the limited spectral resolution in the implant. More specifically, using vocoder simulations, El Boghdady et al.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether CIs could be fitted with the goal of mitigating the effect of decreased spectrotemporal resolution that may arise from channel interaction. Several studies (e.g., Di Nardo et al., 2011 ; El Boghdady et al., 2018 ; Fitzgerald et al., 2013 ; Fu & Shannon, 1999 ; Grasmeder et al., 2014 ; Leigh et al., 2004 ; McKay & Henshall, 2002 ; Omran et al., 2011 ) have proposed that optimizing the frequency-to-electrode allocation map could have the potential to address the limited spectral resolution in the implant. More specifically, using vocoder simulations, El Boghdady et al.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether CIs could be fitted with the goal of mitigating the effect of decreased spectrotemporal resolution that may arise from channel interaction. Several studies (e.g., Di Nardo, Scorpecci, Giannantonio, Cianfrone, & Paludetti, 2011;El Boghdady et al, 2018;Fitzgerald, Sagi, Morbiwala, Tan, & Svirsky, 2013;Fu & Shannon, 1999;Grasmeder, Verschuur, & Batty, 2014;Leigh, Henshall, & McKay, 2004;McKay & Henshall, 2002Omran, Lai, & Dillier, 2011) have proposed that optimizing the frequency-to-electrode allocation map could have the potential to address the limited spectral resolution in the implant. More specifically, using vocoder simulations, El Boghdady et al (2018) have shown that the frequency-to-electrode allocation map could have a direct influence on VTL JNDs, and that the frequency mapping, if optimally fitted, could help reduce the detrimental effects of channel interaction and frequency mismatch in the cochlea on VTL JNDs.…”
Section: Discussionmentioning
confidence: 99%
“…Bierer and Litvak (2016) found improvements in phoneme recognition among some poorer performers when they used a partial tri-polar, as opposed to monopolar, stimulation strategy with either 1) a MAP with a full complement of electrodes (no site-selection) or 2) a site-selection program using monopolar stimulation (Bierer & Litvak, 2016). Grasmeder and colleagues (Grasmeder, Verschuur, & Batty, 2014) demonstrated that frequency-to-electrode assignment using a reduced-frequency MAP based on post-operative x-ray imaging and insertion angle can improve performance in some listeners. Results from Vickers and colleagues argue that site deactivation for n-of-m strategies (e.g., SPEAK, ACE) is not beneficial when choosing stimulation sites based on pitch-ranking tasks.…”
Section: Discussionmentioning
confidence: 99%